The validity and intramodel reliability of the Omron HJ-005 pedometer for quantifying steps in free-living conditions and over a 400-meter walk - Chee, H. P.; Abu Saad, Hazizi; Mohd Yusof, Barakatun Nisak; Mohd Taib, Mohd Nasir (School of Health Sciences, Universiti Sains Malaysia, 2014)
The purpose of this study was to determine the validity and intramodel reliability of the Omron HJ-005 pedometer under free-living conditions and over a 400-meter walk. For the first part of the study, data were analysed from subjects who wore both motion sensors (the Kenz Lifecorder e-Steps accelerometer and the Omron HJ-005 pedometer) during waking hours for two consecutive weekdays and one weekend day. For the second part of the study, subjects walked 400 meters around an outdoor track while wearing two Omron HJ-005 pedometers (one each on the right and left side of the waist and centred over the foot). Under free-living conditions, the subjects reported an averaged 6,588 ± 1,240 accelerometer steps per day and 7,676 ± 1,327 pedometer steps per day. There was a significant correlation between the mean accelerometer outputs and the mean pedometer outputs for two consecutive weekdays and one weekend day (r = 0.954, p < 0.001). The mean difference in steps detected between the Kenz Lifecorder e-Steps accelerometer and the Omron HJ-005 pedometer was 1,088 ± 399 steps per day [t (53) = 20.037, p < 0.001]. On a 400-meter outdoor track, the Omron HJ-005 pedometer reported step counts with an absolute percent error (APE) of less than 5% for pedometers at both the right and left sides of the waist (at slow, moderate and fast paces) compared to manual step counts. Pedometer step counts at the right and left sides of the waist were significantly correlated (intra-class correlation coefficient >0.9) at slow, moderate and fast paces. In conclusion, the Omron HJ-005 pedometer demonstrated validity and intramodel reliability over a 400-meter walk at slow, moderate and fast paces. The correlation between the outputs from the Kenz Lifecorder e-Steps accelerometer and the Omron HJ-005 pedometer supports the interchangeability of the outputs (steps per day) from two motion sensors if only relative values are desired.